AGRIBUSINESS DEVELOPMENT STRATEGY BASED ON REGIONAL SUPERIOR COMMODITIES - Loso Judijanto; Puteri Aprilani (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Developing agribusiness based on regionally superior commodities is a crucial strategy for driving regional economic growth, improving farmer welfare, and strengthening national food security. Each region has distinct natural resource, social, and economic characteristics, necessitating a specific agribusiness development approach based on local potential. This study aims to analyze agribusiness development strategies based on regionally superior commodities through a literature review. The study was conducted by examining various scientific sources, including journal articles, books, research reports, and policy documents relevant to agribusiness development, superior commodities, and regional development. The results indicate that an effective agribusiness development strategy relies on identifying superior commodities with comparative and competitive advantages, strengthening the agribusiness value chain from upstream to downstream, increasing human resource capacity, and providing sustainable policy and institutional support. Furthermore, the integration of technological innovation, market access, and collaboration among stakeholders are key factors in enhancing the competitiveness of agribusiness based on regionally superior commodities. This research is expected to serve as a conceptual reference for policy makers and agribusiness actors in designing adaptive, sustainable agribusiness development strategies that are oriented towards local superior potential.